Monte Carlo methods for particle transport - Haghighat, Alireza (Boca Raton : CRC Press, 2021)
Fully updated with the latest developments in the eigenvalue Monte Carlo calculations and automatic variance reduction techniques and containing an entirely new chapter on fission matrix and alternative hybrid techniques. This second edition explores the uses of the Monte Carlo method for real-world applications, explaining its concepts and limitations. Featuring illustrative examples, mathematical derivations, computer algorithms, and homework problems, it is an ideal textbook and practical guide for nuclear engineers and scientists looking into the applications of the Monte Carlo method, in addition to students in physics and engineering, and those engaged in the advancement of the Monte Carlo methods. Describes general and particle-transport-specific automated variance reduction techniques Presents Monte Carlo particle transport eigenvalue issues and methodologies to address these issues Presents detailed derivation of existing and advanced formulations and algorithms with real-world examples from the author's research activities
OCLC-licensed vendor bibliographic record.
Keywords: Monte Carlo method; Particles (Nuclear physics) -- Mathematical models; Radiative transfer; Transport theory; MATHEMATICS / Probability & Statistics / General; SCIENCE / Energy; SCIENCE / Nuclear Physics